ANALISIS ORIENTASI PELUANG DAN FOKUS PADA PELANGGAN DALAM MENINGKATKAN KEPUASAN KONSUMEN (STUDI KRESNA KAMPUNG INGGRIS PARE) - Nasution, Muhammad Fajar Padlin; Pandiangan, Bilson; br Sinulingga, Nora (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas HKBP Nommensen, 2025)
This study aims to examine the application of opportunity orientation and customer focus on customer satisfaction at Kresna, Kampung Inggris Pare. This study is a descriptive quantitative study, which uses an online survey via Google Forms to collect data and obtained a total of 121 student respondents. The data analysis method used is multiple linear regression analysis. The results of the analysis show that opportunity orientation has a positive and significant effect on customer satisfaction. Customer focus has a positive and significant effect on customer satisfaction. Simultaneously, opportunity orientation and customer focus have a positive and significant effect on customer satisfaction, with a contribution of 61.1%.